Impact of social media advertising features on Vietnamese gen z’s online shopping intentions - Le Tan, Trinh; Xuat, Ngo Tran; Trang, Dao Thi Dai; Tri, Nguyen Duc; Tai, Mai Xuan (ARKA INSTITUTE, 2024)
The growing use of social media has fundamentally transformed the advertising landscape, particularly among youngsters. Understanding the elements that drive online purchase intentions is critical for firms catering to this population. The purpose of this research is to study the impact of social media advertising features on Vietnamese GenZ’s online shopping intentions. (Which examines the theories of source informativeness (INF), Interactivity (INT), Interesting (IR), Viral (VR), Credibility (CRE), Entertainment (ENT) and builds structural models (SEM) with high accuracy.An online survey evaluated the impact of social media advertising features on Vietnamese GenZ’s online shopping intentions. The minimum sample size for this study will be 197 (n=197) by using Google Form. Through the data, CFA and SEM will be conducted by using AMOS software and SPSS. Reliability statistics of the scale will be conducted by using Cronbach's Alpha, EFA and CFA. The result showed that viral advertising significantly impacts consumer behavior by enhancing interest, credibility, and purchasing decisions through widespread content sharing, which increases trust and perceived product quality. The strong interaction between informativeness, virality, and viewer engagement, with virality having the most substantial effect, highlights its critical role in influencing purchase decisions and customer engagement.